Shifts in the Boot: Understanding Inequality’s Impact on Interregional Migration Patterns in Italy - Giacomo Di Pasquale; Elisa Parazzi (Economies)
Italy has long experienced a significant developmental gap between its northern and southern regions, with the latter being less developed. The 2007–2008 financial crisis accentuated this gap, leading to distinct patterns of interregional migration. This paper aims to investigate the effects of past migration flows and income inequality on interregional mobility in Italy, using a gravity model with bidirectional dyads and three different measures of inequality as dependent variables: Gini Index, Relative Poverty, and Income Ratio. Previous research has shown that living in highly unequal regions is associated with increased mistrust and anxiety about social status, contributing to unhappiness among residents. Using bilateral gross migration flows for the period 2007–2018, the study aims to control for the potential endogeneity between interregional mobility and inequality. The results indicate a positive relationship between high levels of inequality and interregional out-mobility, underscoring the need for policies aimed at reducing both horizontal and vertical inequality within and among Italian regions.